2022
DOI: 10.1111/bph.15743
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptide inhibitor of Dll4‐Notch1 signalling and its pro‐angiogenic functions

Abstract: Background and Purpose: The Dll4-Notch1 signalling pathway plays an important role in sprouting angiogenesis, vascular remodelling and arterial or venous specificity.Genetic or pharmacological inhibition of Dll4-Notch1 signalling leads to excessive sprouting angiogenesis. However, transcriptional inhibitors of Dll4-Notch1 signalling have not been described.Experimental Approach: We designed a new peptide targeting Notch signalling, referred to as TAT-ANK, and assessed its effects on angiogenesis. In vitro, tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…The results showed that Dll4, Bmpr2, and Nrf2 were highly expressed in endothelial cells. Inhibition of the Dll4-Notch1 pathway promotes excessive sprouts and endothelial proliferation in the retina (Zhu et al, 2022), and the high expression of Bmpr2 is also conducive to regulating excessive angiogenesis. In an experimental model of Bmpr2 knockout, vascular endothelial cell proliferation was observed (Theilmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that Dll4, Bmpr2, and Nrf2 were highly expressed in endothelial cells. Inhibition of the Dll4-Notch1 pathway promotes excessive sprouts and endothelial proliferation in the retina (Zhu et al, 2022), and the high expression of Bmpr2 is also conducive to regulating excessive angiogenesis. In an experimental model of Bmpr2 knockout, vascular endothelial cell proliferation was observed (Theilmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Dll4 is the only Notch ligand mainly expressed in endothelial cells, especially in arterial endothelial cells [5]. Different from other ligands, Dll4 is cell contact-dependent and can propagate through positive feedback mechanism through activation of Notch signal [6]. Dll4 gene is located on chromosome 15q14, which is a type I single transmembrane protein composed of 685 amino acids.…”
Section: Dll4 Ligand Structurementioning
confidence: 99%
“…In Dll4 heterozygous mice, the haploid mortality was insufficient due to defects in sprouting angiogenesis and arteriovenous formation. So far, Dll4 is the second gene causing hypo haploid death, and the first gene is vascular endothelial growth factor (VEGF), indicating that Dll4 and VEGF play an indispensable role in angiogenesis 6 . The blocking of DLL4 inhibits tumor growth by regulating tumor angiogenesis, which is characterized by promoting pathological activation of endothelial cells and excessive tumor vascular growth without function [8].…”
Section: Dll4 Ligand Structurementioning
confidence: 99%
See 2 more Smart Citations